SISTEM INFORMASI PELAYANAN TEMPAT KOS KAMPUS SEKITAR LINGKUNGAN UPN VETERAN JAKARTA BERBASIS WEB - Early Ariesabilal Satianto (2023)
The role of information technology cannot be separated from the life of modern society. Information technology is designed to help deal with a variety of everyday problems. As the subject of temporary housing, it is most in demand by migrants, students or students around the Jakarta Veterans Development University. These temporary accommodations are better known as boarding houses. Their obstacle is the difficulty in obtaining information about the location of the boarding house. They are limited by their limited knowledge of city and street names. Therefore, by building a web-based application to search for pension funds, it is hoped that the problems faced by prospective retirees can be resolved. This application manages input information and provides detailed and precise location information via Google Maps. In addition, this program also offers benefits for accommodation managers who can market their boarding houses online to the wider community.